Nature shark - Questar (Chicago, Ill.: Questar, 2004)
This program discovers about sharks species, how they hunt their favourite foods and etc.
program 1. The secret world of sharks and rays - program 2. White shark-red triangle
Keywords: White shark -- Juvenile literature; Sharks; Rays (Fishes) -- Juvenile literature